Management of Beta-Lactam Antibiotics Allergy: A Real-Life Study - Iuliano, Sarah; Senn, Laurence; Moi, Laura; Muller, Yannick D.; Ribi, Camillo; Buss, Guillaume; Comte, Denis (Frontiers in Allergy, 2022)
Beta-lactam allergy is a common problem in everyday medical practice and is recognized as a major public health issue. Carrying this label frequently leads to the avoidance of all beta-lactam antibiotics, favoring the use of other less preferred classes of antibiotics, that are more expensive and associated with more side effects and increased antimicrobial resistance. Therefore, delabeling a beta-lactam allergy is part of antimicrobial stewardship programs. Herein, we retrospectively examined the clinical records of 576 patients who were referred to our center for a label of allergy to beta-lactam antibiotics and were systematically investigated following a standardized algorithm. Our main aim was to evaluate the frequency of confirmed immediate- and delayed-type allergy to commonly prescribed subclasses of beta-lactam antibiotics (penicillin and cephalosporin), as well as the negative predictive value (NPV) and the sensitivity of skin tests. Our secondary aims were to examine the safety of beta-lactam skin testing and drug challenge. We identified that 260 patients reported a history of immediate reactions, 131 of delayed reactions, and 114 of unknown timing or mechanism of reactions. Following assessment and testing, 86 (18.3%) patients had a confirmed allergy to any beta-lactam antibiotics; 63 (13.4%) with an immediate- and 23 (4.9%) with a delayed-type reaction. Most frequently identified confirmed allergy was to penicillins (65 patients), followed by cephalosporins (21 patients). When immediate-type reactions were examined, NPV of skin tests were 96.3% and 100% for penicillins and cephalosporins, respectively. When delayed reactions were considered, NPV were 91.9% and 87.5% for penicillins and cephalosporins, respectively. Evaluation of the safety of skin tests according to the standardized procedure showed that systemic allergic reactions occurred in only 0.7% of skin tests and in 3.1% of drug challenges. Overall, our data indicate that only 18.3% of patients with a beta-lactam allergy label have a confirmed allergy and non-allergic patients can be safely delabeled through allergic workup based on skin tests and drug challenge. This approach supports the policy of saving second-line antibiotics through a standardized allergy workup.